Prevalence of cerebro-vascular disease in patients of peripheral arterial occlusive disease - Mahapatra, Sandeep; Ramakrishna, Pinjala; Kumar, G. V. Praveen (International Surgery Journal, 2016)
Background:Peripheral arterial occlusive disease (PAOD) is a surrogate marker of systemic atherosclerosis which also predicts the risk of cerebro-vascular disease (CVD). Methods: We have conducted a prospective study in 100 symptomatic PAOD patients between 18 to 65 years of age for detection of CVD over a period of two years. Segmental blood pressure and pulse volume recording, Duplex ultrasound blood flow of the peripheral arterial system and carotid arteries were done along with evaluation for risk factors of atherosclerosis i.e., hypertension, diabetes mellitus, hyperlipidemia, smoking history. Results:Mean age 51.83±13.17 with history of smoking (68%), followed by diabetes (57%), dyslipidemia (29%) and hypertension in (23%) of patients.78% of the patients had PAOD in lower limbs. Overall, 30% of the patients had carotid artery stenosis, out of which 17% had less than 50% stenosis of the carotid artery and 13%had greater than 50% stenosis of the carotid artery. 30.8% of patients with lower limb disease and 60% of the patients with aorto-iliac disease had carotid artery disease. Conclusions:This association of PAOD with CVD is significant, indicating regular screening in patients of athererosclerotic PAOD .This is further increased with age, and the presence of hypertension and smoking. We could not establish any association with diabetes, dyslipidemia in the prevalence of CVD in our subset of patients with PAOD.